INDUSTRI DAN PERDAGANGAN GULA DI INDONESIA: PEMBELAJARAN DARI KEBIJAKAN ZAMAN PENJAJAHAN – SEKARANG (Forum Penelitian Agro Ekonomi, 2017)
Sugarcane industry and trade (SIT) in Indonesia is significantly influenced by the government policies. This paper reviewed SIT policies from colonial period up to now to obtain valuable lessons for future development of SIT.  Lessons learned include: (1) During the colonial era, the peak triumph was achieved through farmers’ sacrifice; (2) High financial support for research institutions to produce super varieties, such as POJ 2838 and 3016 with productivity as high as 18 ton/ha of crystal; (3) In the beginning of independence, Indonesia’s institutions and manpower were not exclusively ready to optimally develop SIT; (4) There were no comprehensive policies and several of the existing one were conflicting. Based on these lessons, a comprehensive policy issued by related institutions are strongly required for future development of SIT.